A population based cross sectional study of perception towards snakes and A population based cross sectional study of perception towards snakes and management of snakebites - Doshi, Sunil M; Ravaliya, Hetal; Rangpariya, Rahul; Relia, Rushal; Raninga, Jeet; Raninga, Meet; Rathore , Brinda (Journal of Indian Academy of Forensic Medicine, 2019)
Considering few of the oldest myths and primitive medical writings, snakebite must have been one of its first kinds of poisoning  known to mankind. India is known for its mythological concepts and traditional methods of treatment in regards to snakes and  snakebites. Aim of this study was to evaluate awareness of the urban and rural population towards snakes and snakebite management.  The present study was a cross sectional study conducted on urban and rural population in Gujarat state. Total 240 adult participants,  120 from urban areas and 120 from rural areas, were included in the study. Data was collected by personal interview of an individual  with predefined data collection sheet which was comprised of three parts i.e. demographic information of participants, identification  of snakes in terms of venomicity and pre-defined questionnaire. Prevalence of belief in regards to mythological significance of snakes  is higher in rural in comparison to urban population. As far as identification of nature of snakes is concerned study found below  average knowledge with marginally higher in rural areas. Both the population considers medical measures as an ultimate management  for snakebites. However, perception in relation to first aid measures, identifying nature of snakes, do's and don'ts with a snake as well  as with a case of snake bite need a serious attention especially towards usage of traditional methods.
Keywords: Snake; Snakebite; Population; Perception; Traditional Methods